The Legality of Distributor Incentive Discount Plans Under the Robinson-Patman Act - Thomas A. Piraino Jr. (Washington University Law Quarterly, 1980)
This Article will examine whether sales incentive plans nevertheless may be justified under the "availability" defense which has been judicially engrafted into the Robinson-Patman Act.
Keywords: Antitrust law; Price regulations; Unfair competition; Robinson-Patman Act; United States